Purity and danger : an analysis of concepts of pollution and taboo - Douglas,Mary (London, 1966)
All religions have rules of purity, heglect of which is punished by dangers of various kinds. The fashion of the last century was to take them for misguided systems of hygiene. Anthropologists now interpret them as symbolic statements. Rules of purity are often treated as peculiar to primitive, foreign thought systems; but, from the starting point of modern ideas of uncleanness and dirt, Professor Douglas shows that to examine what is considered as unclean in any culture is to take a looking-glass approach to the ordered patterning which it strives to establish. Such an approach affords a more universal understanding of rules of purity, applying equally to secular and to religious life, to primitive and modern.
Keywords: Taboo